Odpowiedzi

2010-04-10T17:24:01+02:00
2010-04-10T17:24:51+02:00
27x+19-2x(1-x)=6x-2x(3+2x)
27x+19-2x+2x(2)=6x-6x-4x(2)
25x+2x(2)+4x(2)=-19
25x+6x(2)=-19
myslę, że tu powinno wyjść 25x-6xi wedy ładnie by wyszło, ale tak nie wychodzi

21x+16-x(1-x)=5x-x(1-x)
21x+16-x+x(2)=5x-x+x(2)
21x-5x=-16
16x=-16
x=-1
2010-04-10T17:38:24+02:00
27x+19-2x(1-x)=6x-2x(3+2x)
27x+19-2x+2x2(kwadrat)=6x-6x-4x2(kwadrat)
27x-2x+2x2(kwadrat)-6x+6x+4x2(kwadrat)=-19
25x+6x2(kwadrat)=-19
31x*x=-19 I :31
x*x/31=- 19/31
2/31 x=-19/31 I :2/31
x=-9 i 1/2

2.
21x+16-x(1-x)=5x-x(1-x)
21x+16-x+x2(kwad.)=5x-x+x2(kwad.)
16x= -16 I :16
x=-1